2013
DOI: 10.1002/jsfa.5921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar urea fertilisation on volatile compounds in Tempranillo wine

Abstract: It may be concluded that foliar urea fertilisation shows itself to be efficient in small doses as a complement to soil fertilisation to improve wine aroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 28 publications
2
36
1
Order By: Relevance
“…The absence of significant differences regarding the remaining parameters is in contrast to the study conducted by Ancín-Azpilicueta et al (2013). The latter study showed that foliar application of 2 kg N/ha of urea in a Tempranillo vineyard led to an increase in pH and a reduction of alcoholic strength and total acidity in wine that were even more significant when the dose of urea was greater (4 kg N/ha).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The absence of significant differences regarding the remaining parameters is in contrast to the study conducted by Ancín-Azpilicueta et al (2013). The latter study showed that foliar application of 2 kg N/ha of urea in a Tempranillo vineyard led to an increase in pH and a reduction of alcoholic strength and total acidity in wine that were even more significant when the dose of urea was greater (4 kg N/ha).…”
Section: Resultsmentioning
confidence: 59%
“…For instance, Fernández et al (2013) detailed some of them, including plant species, leaf cuticular composition, plant phenology, environmental aspects, or phloem mobility. Research in viticulture has shown that foliar application of urea may modify the wine aroma profile (Ancín-Azpilicueta, Nieto-Rojo, & Gómez-Cordón, 2013) or improve must nitrogen composition (Garde-Cerdán et al, 2014). In the latter work, the application of phenylalanine led to a similar enhancement of must nitrogen composition in comparison with urea application.…”
Section: Introductionmentioning
confidence: 96%
“…reported that these treatments applied to grapevines allowed ethyl hexanoate, ethyl octanoate, and ethyl decanoate content in wines to increase. Ancín‐Azpilicueta et al . showed that the total concentration of higher alcohols in wines decreased with the application of urea in the vineyard, whereas the concentrations of ethyl hexanoate, ethyl octanoate, and ethyl decanoate were highest in the wine obtained from grapevines treated with 4 kg N ha −1 of urea.…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
“…A high nitrogen fertilisation rate in the vineyard can result in lower accumulation of secondary metabolites, due to competition between the vegetative and reproductive tissues . In wines, urea foliar applications to Tempranillo grapevines resulted in a decrease in the content of higher alcohols, while improving the ethyl ester concentration . Moreover, low‐dose urea treatment increased the content of several volatile compounds, except C 6 compounds.…”
Section: Biostimulants To Improve Grape and Wine Qualitymentioning
confidence: 99%